Multifunctional properties of Zn0·9Mn0.05M0.05O (M = Al, Bi, Sr, Ag) nanocrystals-structural and optical study: Enhance sunlight driven photocatalytic activity. Issue 14 (1st October 2020) - Munawar, Tauseef; Mukhtar, Faisal; Nadeem, Muhammad Shahid; Asghar, M.; Mahmood, Khalid; Hussain, Altaf; Arshad, M.I.; Ajaz un Nabi, Muhammad; Iqbal, Faisal
Abstract: Novel Zn0 · 95 Mn0 · 05 O and Zn0 · 9 Mn0.05 M0.05 O (M = Al, Bi, Sr, Ag) nanocrystals were prepared via the co-precipitation technique. The X-ray diffraction pattern confirmed the substitution of Mn, Al, Bi, Sr, and Ag dopants without altering the basic ZnO structure. The microstructural study was performed by employing the Scherrer plot, Williamson-Hall, and SSP methods. The energy bandgap calculated from UV–vis spectra using different methods observed red-shifted by co-doping. The other optical parameters were also studied and discussed in detail. The FTIR spectra confirmed the presence of Zn–O, and Zn-M–O vibrational modes. Raman spectra demonstrated the presence of ZnO phonon modes, and the Raman shift exhibited the structural defects induced by dopants. The PL spectra showed strong NBE and DLE in the UV and visible region due to extrinsic defects. The IV measurements exhibited the enhancement in the electrical conductivity of ZnO by co-doping. The photocatalytic activity was performed under direct sunlight for methyl orange and methylene blue dyes, and the enhanced degradation efficiency was achieved by co-doping. Furthermore, this article enhances the understanding of tuning the physical properties of ZnO by co-doping and introduces a new class of sunlight-driven photocatalysts.